Theory and practice of hydrocarbon generation within space-limited source rocks - Guan, Defan; Xu, Xuhui; Li, Zhiming; Zheng, Lunju; Tan, Caiping; Yao, Yimin (Springer, 2016)
This book analyzes hydrocarbon generation and accumulation within space-limited source rocks. The authors draw conclusions based on the principles of basin formation, hydrocarbon generation and accumulation, coupled with the practice of terrigenous basins in eastern China. Hydrocarbon generation and expulsion have been quantitatively assessed in space-limited source rock systems. This book explores new hydrocarbon generation and expulsion models to reflect real geological situations more accurately. The theory and practice proposed in this book challenge the traditional theory of kerogen thermal degradation and hydrocarbon generation.
"Translation from the Chinese language edition."
Keywords: Petroleum -- Geology.; Hydrocarbons.; Hydrocarbon reservoirs.; elektronické knihy; electronic books